QUR'ANIC AUDITORY STIMULATION AS COGNITIVE-LINGUISTIC THERAPY FOR LEXICAL RETRIEVAL IN POST-STROKE BROCA'S APHASIA: A CASE STUDY - Lilis Hartini; Marsandi Manar; Nur Fathiyya Zahira Mujahidah (Indonesian EFL Journal, 2026)
Post-stroke aphasia impairs lexical retricceeeval, verbal fluency, and communication ability, yet access to conventional speech therapy remains limited in many developing countries. This study examined whether Qur'anic recitation therapy could facilitate cognitive-linguistic recovery in a patient with Broca's aphasia, focusing specifically on lexical retrieval mechanisms. A qualitative case study design was employed, involving a 43-year-old male lecturer from West Java, Indonesia, who experienced a hemorrhagic stroke affecting Broca's area, resulting in non-fluent aphasia. The participant, a native Sundanese-Indonesian speaker with pre-stroke Qur'anic memorization experience, received structured therapy over approximately 71 days. The intervention comprised five stages: ablution procedures, prayer movements, recitation of short surahs (Al-Fatihah, Al-Ikhlas, Al-Falaq, An-Nas), dhikr verbal repetition, and daily prayers. Data were collected through observation of verbal production during therapy sessions and analyzed qualitatively, focusing on lexical retrieval accuracy, verbal fluency, and communication confidence. Findings revealed that the participant successfully retrieved familiar Qur'anic recitations more accurately than unfamiliar Indonesian texts, indicating that spiritually embedded language stored in long-term memory remained relatively preserved. Gradual improvements in attention, verbal recall, and communicative confidence were observed. Within one year post-therapy, the participant resumed employment, served as a muezzin, and completed a master's degree. The study concludes that Qur'anic recitation may function as cognitive-linguistic stimulation supporting lexical retrieval in post-stroke aphasia through mechanisms of familiarity, repetition, and semantic cueing. However, these findings derive from a single case and require replication. Recommendations include integrating spiritually familiar linguistic stimuli into aphasia rehabilitation protocols, conducting controlled group studies, and exploring applicability across different aphasia types and cultural-linguistic contexts.